Significance of dark CO2 fixation in arctic soils. (April 2018) - Šantrůčková, Hana; Kotas, Petr; Bárta, Jiří; Urich, Tim; Čapek, Petr; Palmtag, Juri; Eloy Alves, Ricardo J.; Biasi, Christina; Diáková, Kateřina; Gentsch, Norman; Gittel, Antje; Guggenberger, Georg; et al.
Abstract: The occurrence of dark fixation of CO2 by heterotrophic microorganisms in soil is generally accepted, but its importance for microbial metabolism and soil organic carbon (C) sequestration is unknown, especially under C-limiting conditions. To fill this knowledge gap, we measured dark 13 CO2 incorporation into soil organic matter and conducted a 13 C-labelling experiment to follow the 13 C incorporation into phospholipid fatty acids as microbial biomass markers across soil profiles of four tundra ecosystems in the northern circumpolar region, where net primary productivity and thus soil C inputs are low. We further determined the abundance of various carboxylase genes and identified their microbial origin with metagenomics. The microbial capacity for heterotrophic CO2 fixation was determined by measuring the abundance of carboxylase genes and the incorporation of 13 C into soil C following the augmentation of bioavailable C sources. We demonstrate that dark CO2 fixation occurred ubiquitously in arctic tundra soils, with increasing importance in deeper soil horizons, presumably due to increasing C limitation with soil depth. Dark CO2 fixation accounted on average for 0.4, 1.0, 1.1, and 16% of net respiration in the organic, cryoturbated organic, mineral and permafrost horizons, respectively. Genes encoding anaplerotic enzymes of heterotrophic microorganisms comprised the majority of identified carboxylase genes. The genetic potential for dark CO2 fixation was spread over a broad taxonomic range. The results suggest important regulatory function of CO2 fixation in C limited conditions. The measurements were corroborated by modeling the long-term impact of dark CO2 fixation on soil organic matter. Our results suggest that increasing relative CO2 fixation rates in deeper soil horizons play an important role for soil internal C cycling and can, at least in part, explain the isotopic enrichment with soil depth. Highlights: The dark CO2 fixation is a common process in arctic soils. Its importance increases in deeper soil horizons. Mainly heterotrophic microorganisms are responsible for dark CO2 fixation. The genetic potential for dark CO2 fixation is spread over a broad taxonomic range. Dark CO2 fixation can partly explain the isotopic enrichment of SOM with soil depth.